Conflict without an apparent cause - Timothy Mathews; Aniruddha Bagchi (Games, 2019)
A game-theoretic model of repeated interaction between two potential adversaries is analyzed to illustrate how conflict could possibly arise from rational decision-makers endogenously processing information, without any exogenous changes to the fundamentals of the environment. This occurs as a result of a convergence of beliefs about the true state of the world by the two players. During each period, each adversary must decide to either stage an attack or not. Conflict ensues if either player chooses to initiate an attack. Choosing to not stage an attack in a given period reveals information to the player's rival. Thus, over time, beliefs about the true state of the world converge. Depending upon the true state of the world, we can ultimately have either of the two adversaries initiating an attack (either with or without regret) after an arbitrarily long period of tranquility. When this happens, it is as if conflict has suddenly arisen without any apparent cause or impetus. Alternatively (again, depending upon the true state of the world), we could possibly have beliefs converge to a point where neither adversary wants to initiate conflict.
Keywords: 330; conflict; game theory; knowledge